The utility of impedance cardiography in hemodynamic monitoring of patients with sepsis - James Butz; Yizhi Shan; Andres Samayoa; Orlando C Kirton; Thai Vu (Trauma Surgery & Acute Care Open, 2019)
Background Commonly used biochemical indicators and hemodynamic and physiologic parameters of sepsis vary with regard to their sensitivity and specificity to the diagnosis. The aim of this preliminary study was to evaluate non-invasive impedance cardiography as a monitoring tool of the hemodynamic status of patients with sepsis throughout their initial volume resuscitation to explore the possibility of identifying additional measurements to be used in the future treatment of sepsis.Methods Nine patients who presented to the emergency room and received a surgical consultation during a 3-month period in 2016, meeting the clinical criteria of sepsis defined by systemic inflammatory response syndrome in the 2012 Surviving Sepsis Campaign Guidelines, were included in this study. We applied cardiac impedance monitors to each patient’s anterior chest and neck and obtained baseline recordings. Measurements were taken at activation of the sepsis alert and 1 hour after fluid resuscitation with 2 L of intravenous crystalloid solution.Results Nine patients met the inclusion criteria. The mean age was 60±17 years and two were female; eight were febrile, five were hypotensive, four were tachycardic, seven were treated for infection, and six had positive blood cultures. Hemodynamic parameters at presentation and 1 hour after fluid resuscitation were heart rate (beats per minute) (97±13 and 93±18; p=0.23), mean arterial pressure (mm Hg) (81±13 and 85±14; p=0.55), systemic vascular resistance (dyne-s/cm−5) (861±162 and 1087±272; p=0.04), afterload measured as systemic vascular resistance index (dyne-s/cm−5/m2) (1813±278 and 2283±497; p=0.04), and left cardiac work index (kg*m/m2) (3.6±1.4 and 3.3±1.3; p=0.69).Discussion Through measuring a patient’s systemic vascular resistance and systemic vascular resistance index (afterload), statistical significance is achieved after intervention with a 2 L crystalloid bolus. This suggests that, along with clinical presentation and biochemical markers, impedance cardiography may show utility in providing supporting hemodynamic data to trend resuscitative efforts in patients with sepsis.Level of evidence Level IV.